2001
DOI: 10.1021/jp003862v
|View full text |Cite
|
Sign up to set email alerts
|

Collision-Induced Desorption and Reaction on Hydrogen-Covered Al(111) Single Crystals:  Hydrogen in Aluminum?

Abstract: We examine the recombination and desorption of hydrogen from an aluminum(111) surface focusing on desorption processes that lead to the formation of dihydrogen and aluminum hydride (presumably alane). In addition to simple temperature-programmed reaction spectroscopy (TPRS), we examine the perturbations which occur to the desorption kinetics of these species as a result of the energy transfer due to collisions of a xenon beam at 1.6, 2.8, and 3.6 eV with a hydrogen covered surface. Whereas the recombinative de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 66 publications
(146 reference statements)
1
16
0
Order By: Relevance
“…and the H-induced etching of aluminum to form hydride, as has been extensively observed in vacuum experiments [25][26][27][28][29][30] Al + 3H → AlH 3 ͓3͔…”
Section: ͓1͔mentioning
confidence: 74%
“…and the H-induced etching of aluminum to form hydride, as has been extensively observed in vacuum experiments [25][26][27][28][29][30] Al + 3H → AlH 3 ͓3͔…”
Section: ͓1͔mentioning
confidence: 74%
“…[13][14][15][16][17][18] The hydride then oxidized according to the reaction identified by Perrault The present paper examines whether the electrochemical behavior of anodic Al dissolution in alkaline solutions supports the participation of AlH 3 as a reaction intermediate. Results of cyclic voltammetry ͑CV͒ and potential step experiments are interpreted using models for the Al electrode based on the proposed mechanism.…”
Section: Al + 3h → Alh 3 ͓2͔mentioning
confidence: 99%
“…These findings are important because light metals such as aluminum are inexpensive and can store large amounts of hydrogen, which is crucial for fuel cell design [4]. Crane and Nuzzo [5] obtained evidence related to H adsorption on Al(1 1 1). Through careful examination of temperature-programmed desorption data, they suggested that chemisorbed H on Al(1 1 1) occupies both surface and subsurface sites.…”
Section: Introductionmentioning
confidence: 99%